1990
DOI: 10.1109/49.57813
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk analysis and filter optimization of single- and double-cavity Fabry-Perot filters

Abstract: Fabry-Perot Filters are major candidates for use as demultiplexers in wavelength division multiple access networks. In this paper we investigate the crosstalk limitations of such filters, compare their performances, and optimize the filter design to minimize the crosstalk degradation.1 Bol.h witli the al)()rt;l.orlo for informltaiou a.icl I)ecision Ssleties. ilT. C(amlridge. hi\ 02139. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 10 publications
4
42
0
Order By: Relevance
“…The above formulas agree precisely with our previous results in [2], where we assumed a = 0 (i.e., zero-bandwidth or tone-like channels). In that case the signal energy and the crosstalk are given by 1 and 12 (M)2 respectively.…”
Section: Penalty Calculationssupporting
confidence: 80%
See 2 more Smart Citations
“…The above formulas agree precisely with our previous results in [2], where we assumed a = 0 (i.e., zero-bandwidth or tone-like channels). In that case the signal energy and the crosstalk are given by 1 and 12 (M)2 respectively.…”
Section: Penalty Calculationssupporting
confidence: 80%
“…In effect then, an input impulse "sees" exactly 2 In contrast to our analysis of the FP filter model, we shall find it more convenient to express our results in terms of , instead of c. However, these two quantities are dependent variables here since, by using (37),…”
Section: Temporal Responsesmentioning
confidence: 97%
See 1 more Smart Citation
“…An example of a mechanically tuned etalon is the Fabry-Perot filter. In [23], it was found that the maximum number of channels for a single-cavity Fabry-Perot filter is 0.65 , where is the finesse. A twopass filter was found to have a maximum of 1.4 channels, and two-cavity filters up to 0.44 channels.…”
Section: B Tunable Optical Filtersmentioning
confidence: 99%
“…where y1'i = e2i + e2 and 72i = (Eli -e2i) 2 . The filtering plus crosstalk penalty, on the other hand, depends only on the yli and equals 10 log 10…”
Section: Imperfect Coupling Ratiosmentioning
confidence: 99%